The Oxford history of the classical world (Oxford, New York, 1986)
The book gives a comprehensive view of the Graeco-Roman world, its history and its achievements. After a general introduction ther are three main sections. The first, Greece, runs from the eighth to the fourth centuries B.C., a period inparalleled in history for its brillance in literature, philisophy, and the visual arts. The second, Grecce and Rome, deals with the Hellenization of the Middle East by the monarchies established in the area conquered by Alexander the Great, the growth of Rome, and the impact of the two cultures on one another. The third, Rome, covers the foundation of the Romen Empire by Augustus and its consolidation in the first two centuries A.C., while an envoi discusses some aspects of the later Empire and its influence on western civilization. Each section chapters dealing with political and social history are interspersed with chapters on literature, philosophy, and the arts; the history framework is reinforced by maps and chronological charts. There are bibliographies and a full index; and the book is illustrated with 16 pages of colour plates and over 250 black and white illustrations integrated with the text
Keywords: civilization, classical,history, ancient